A dynamically adaptive lattice Boltzmann method for thermal convection problems - Feldhusen, Kai; Deiterding, Ralf; Wagner, Claus (Zielona Góra: Uniwersytet Zielonogórski)
Utilizing the Boussinesq approximation, a double-population incompressible thermal lattice Boltzmann method (LBM) for forced and natural convection in two and three space dimensions is developed and validated. A block-structured dynamic adaptive mesh refinement (AMR) procedure tailored for the LBM is applied to enable computationally efficient simulations of moderate to high Rayleigh number flows which are characterized by a large scale disparity in boundary layers and free stream flow.
Keywords: lattice Boltzmann method; adaptive mesh refinement; thermal convection; incompressible